1983
DOI: 10.1016/s0190-9622(83)70192-1
|View full text |Cite
|
Sign up to set email alerts
|

Surgical antiseptics

Abstract: The skin cannot be sterilized because approximately 20% of the resident flora are beyond the reach of surgical scrubs and antiseptics. The goal of surgical preparation of the skin with antiseptics is to remove transient and pathogenic microorganisms on the skin surface and to reduce the resident flora to a low level. Four antiseptics which have been popular over the past two decades are discussed. Benzalkonium chloride is somewhat unstable on the skin and is too prone to contamination to be in general use. Hex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
4

Year Published

1985
1985
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 53 publications
0
21
0
4
Order By: Relevance
“…We observed that most infants with detectable serum chlorhexidine concentrations had their highest measured concentrations 2 to 3 days after exposure. Chlorhexidine is a cationic biguanide that strongly binds to protein in the outermost layer of the skin, which contributes to its effectiveness as an antimicrobial agent (16). Hexachlorophene, another antimicrobial agent that leaves a residue on the skin, has also been shown to have delayed absorption in neonates (17).…”
Section: Discussionmentioning
confidence: 99%
“…We observed that most infants with detectable serum chlorhexidine concentrations had their highest measured concentrations 2 to 3 days after exposure. Chlorhexidine is a cationic biguanide that strongly binds to protein in the outermost layer of the skin, which contributes to its effectiveness as an antimicrobial agent (16). Hexachlorophene, another antimicrobial agent that leaves a residue on the skin, has also been shown to have delayed absorption in neonates (17).…”
Section: Discussionmentioning
confidence: 99%
“…Chlorhexidine more strongly binds to protein in the outermost layer of the skin, withstanding removal by alcohol and immediately decreasing organisms on the skin after one application. 18 Although numerous studies have assessed CHG absorption in term infants with no reports of neurotoxicity, residual concerns have limited its use in some hospitalized neonates, especially low birth weight preterm infants. 19 This population with increased vulnerability to infection may benefit from the antiseptic effects of CHG.…”
Section: Historical Perspective On Chg Safety In Neonatesmentioning
confidence: 99%
“…O álcool iodado a 1 ou 2% é germicida de largo espectro, mesmo para esporulados; apesar de eficaz e barato não possui efeito residual e pode provocar reação dermatológica de hipersensibilidade em alguns pacientes. Os derivados da clorhexidina têm atividade antibacteriana duradoura, ação residual e raramente provocam reação alérgica 7 , mas podem custar mais que os iodofóricos.…”
Section: Os Pacientes Asa 2 Eunclassified